2023
DOI: 10.3233/nre-220216
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up visits after a concussion in the pediatric population: An integrative review

Abstract: BACKGROUND: Concussions are a significant health issue for children and youth. After a concussion diagnosis, follow-up visits with a health care provider are important for reassessment, continued management, and further education. OBJECTIVE: This review aimed to synthesize and analyse the current state of the literature on follow-up visits of children with a concussive injury and examine the factors associated with follow-up visits. METHODS: An integrative review was conducted based on Whittemore and Knafl’s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is a feasible service demonstrated by a follow-up completion rate of 79.5% despite a wide range of residential locations (maximum of 958.3 miles from the hospital). This completion rate is on the higher end of follow-up visit rates compared to in-person concussion clinics discussed in a recent review by Ramsay et al, who reported a rate of follow-up visits across nine in-person clinics ranging from 13.2-99.5%, four clinics with completion rates > 50% and ve clinics < 50% [22]. This suggests a virtual model is not only reasonable but allows for a high rate of follow-up completion compared to urban locations.…”
Section: Effectiveness Of a Virtual Clinicmentioning
confidence: 79%
See 2 more Smart Citations
“…It is a feasible service demonstrated by a follow-up completion rate of 79.5% despite a wide range of residential locations (maximum of 958.3 miles from the hospital). This completion rate is on the higher end of follow-up visit rates compared to in-person concussion clinics discussed in a recent review by Ramsay et al, who reported a rate of follow-up visits across nine in-person clinics ranging from 13.2-99.5%, four clinics with completion rates > 50% and ve clinics < 50% [22]. This suggests a virtual model is not only reasonable but allows for a high rate of follow-up completion compared to urban locations.…”
Section: Effectiveness Of a Virtual Clinicmentioning
confidence: 79%
“…Additionally, with a median follow-up time of 4.5 days, our clinic suggests that a virtual model excels in allowing providers to expedite the time it takes to provide follow-up care to patients who suffer a traumatic brain injury. In the same review, median follow-up times among eight in-person clinics were reportedly ranging from 4 days to 1.2 months [22], and interestingly, record of this important metric in concussion follow-up care is often not well represented in the literature, as only 8 of the 23 clinics cited in this review reported this data.…”
Section: Effectiveness Of a Virtual Clinicmentioning
confidence: 89%
See 1 more Smart Citation